1983
DOI: 10.1016/0014-5793(83)80506-7
|View full text |Cite
|
Sign up to set email alerts
|

Binding specificities of the lectins from Helix pomatia, soybean and peanut against different glycosphingolipids in liposome membranes

Abstract: The binding specificities of the lectins from Helixpomatia, soybean and peanut against glycosphingolipids containing Blinked terminal D-galactose and N-acetyl-D-galactosamine and the role of sialic acid as a modulator of the binding specificity were investigated. The test system used consisted of liposomes containing the glycosphingolipids and lectins coupled to gel columns. Of the investigated glycosphingolipids only ganglioside GM2 bound to soybean agglutinin while Heiixpomatia agglutinin was found to bind o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…WGA is a lectin that has high affinity for N-acetylglucosamine and N-acetylneuraminic acid moieties present on surface proteins (30) and is efficiently endocytosed (5,10,42). It has been shown that most WGA inoculated intramuscularly (into the flexor forelimb muscle) is transported retrogradely to the motor neuron cell bodies located in the ventral horn of the spinal cord in mice (4).…”
Section: Resultsmentioning
confidence: 99%
“…WGA is a lectin that has high affinity for N-acetylglucosamine and N-acetylneuraminic acid moieties present on surface proteins (30) and is efficiently endocytosed (5,10,42). It has been shown that most WGA inoculated intramuscularly (into the flexor forelimb muscle) is transported retrogradely to the motor neuron cell bodies located in the ventral horn of the spinal cord in mice (4).…”
Section: Resultsmentioning
confidence: 99%
“…WGA, the lectin used in the present study, binds to sialic acid when the acid is present at certain specific positions of the oligosaccharide (M~nsson & Olofsson, 1983). When the effects of three compounds (taxol, nocodazole and EHNA) on the neuritic transport of WGA and HSV in rat sensory neurons were compared, all three were found to have an equal blocking capacity in the lectin and the virus systems.…”
mentioning
confidence: 89%
“…The glycopeptides in the Vt peak most probably contained O-linked oligosaccharides because of their small Mr and because they contained a large amount of GaIN (data not shown). Three lectins (HPA, PNA and WGA) were used: HPA is specific for terminal N-acetylgalactosamine (Hammarstrom et al, 1977;Goldstein & Hayes, 1978); PNA has a narrow specificity for the terminal disaccharide sequence GaI(1-3)GalNAc (Goldstein & Hayes, 1978, Mansson & Olofsson, 1983; WGA has affinity for non-reducing terminal sialic acid and GlcNAc residues (Peters et al, 1979). Analysis of gC-II glycopeptides from SF or U-373MG cells showed that they have very little affinity for HPA lectin ( Fig.…”
Section: Lectin Analysis Of Vt Peak Obtained From Infected U-373mg Anmentioning
confidence: 99%